Use of a Semi-Precision Attachment to Fabricate A Removable Partial Denture: A Case Report - Pandey, Bijay; Joshi, S P; Thapa, D; Shrestha, P (Journal of Nepalese Prosthodontic Society, 2019)
Use of attachment in providing retention to removable prosthesis is an old treatment modality with better success. It highly improves the comfort, aesthetic, function, and patient satisfaction, especially in the patients with long span edentulism where implants and fixed partial denture (FPD) are not indicated and cast partial dentures are barely satisfactory. Proper diagnosis and treatment planning is necessary for selection of appropriate attachment type. A comprehensive evaluation, multi-disciplinary approach and sequential treatment planning is needed for long-term successful outcome. This case report describes the use of an extra coronal semi-precision attachment to enhance retention of removable prosthesis.